Growth performance, carcass characteristics and meat quality of different beef breeds in typical Finnish production systems : Doctoral Dissertation - Pesonen, Maiju (Natural Resources Institute Finland (Luke), 2020)
Beef production in Finland is mostly based on dairy breeds. However, the decrease in the dairy cattle population observed in recent years threatens to reduce the level of beef production. Therefore the beef production chain is making heavy investments in suckler cow production. Although the number of beef cows has increased by 20% over the last 10 years in Finland, there is a clear discrepancy between the demand for and supply of domestic beef. Consequently, slaughterhouse pricing favours heavy carcasses and the average carcass weights of slaughtered animals have increased in recent years. The current situation is challenging because the carcass fatness generally increases with higher carcass weights, and in Finland consumers generally favour low-fat products in beef markets. There is a paucity of information on the effects of the breed on the performance, carcass characteristics and meat quality of beef breed bulls raised to heavy carcass weights, which is a typical Finnish practice. Therefore, the first aim of this thesis was to evaluate the growth performance, carcass traits and meat quality of different beef breeds in the Finnish beef cattle population. The second aim was to evaluate the potential for improvement of carcass and meat quality traits through crossbreeding compared to purebred animals. The third objective was to evaluate carcass fat scores in relation to carcass weights in different breed groups. In addition, the effects of the proportion of concentrates and rapeseed meal (RSM) supplementation on animal performance, carcass characteristics and meat quality parameters were determined for Hereford (Hf) and Charolais (Ch) bulls. To achieve these aims five experiments were carried out. The objectives of the first experiment, in which Hf and Ch bulls were offered grass silage-based diets, were to determine the effects on the performance, carcass traits and meat quality of the proportion of concentrate in the diet, and the inclusion of RSM in a barley-based concentrate. The two concentrate proportions were 200 and 500 g/kg of dry matter fed with or without RSM. The Ch bulls tended to achieve higher gains, produce less fat, had a higher percentage of meat for highly priced joints and had a lower degree of marbling in their meat compared to the Hf bulls. The dry matter and energy intake, growth performance and carcass conformation improved with increasing concentrate levels. Rapeseed meal supplementation had only limited effects on the performance, carcass traits or meat quality. The objective of the second experiment was to study performance and meat quality of purebred Hf and Ch bulls and Hf × Ch crossbred bulls which were offered grass silage-grain-based rations and raised to heavy carcass weights. The average slaughter age for all breeds was 565 days and the mean carcass weights for Hf, Hf × Ch and Ch bulls were 414, 476 and 507 kg, respectively. The Ch bulls tended to achieve higher weight gains, produced less fat and had a higher percentage of valuable cuts compared to the Hf bulls. The breed group had no significant effects on the beef flavour, but the tenderness and juiciness were better in the meat of the Hf bulls than that of the Ch bulls. The crossbred Hf × Ch bulls produced heavier and better conformed carcasses compared to pure Hf bulls, which indicates that this type of crossbreeding can enhance beef production under the conditions studied. The objective of the third experiment was to study the performance, carcass traits and meat quality of purebred Aberdeen Angus (Ab) and Limousin (Li) bulls and Ab × Li crossbred bulls. The average slaughter age for all breeds was 540 days and the mean carcass weights for the Ab, Ab × Li and Li bulls were 391, 399 and 439 kg, respectively. The Li bulls tended to achieve a higher conformation score, produced less fat and had a higher percentage of valuable cuts compared to the Ab bulls. The crossbred Ab × Li bulls produced better conformed carcasses and a higher share of the rounds compared to the pure Ab bulls. The objective of the fourth experiment was to determine the growth and carcass traits of beef breed bulls and heifers. The data collected from Finnish slaughterhouses included observations of 6 323 and 2 385 Hf (bulls and heifers, respectively), 4 421 and 1 794 Ch, 4 335 and 1 951 Li, 4 068 and 1 692 Ab, 2 151 and 774 Simmental (Si), 344 and 147 Blonde d’Aquitaine (Ba) animals. For estimating valuable cuttings, a separate dataset including 1 112 bulls and 260 heifers in total was also collected. The later maturing, Continental breeds seemed to reach higher carcass gains, produce less fat and have more valuable cuts than the earlier maturing British breeds. The later maturing beef breeds tended to have carcass traits that suit the Finnish beef production system well. The objective of the fifth experiment was to study the potential for improvement in the gain and carcass traits through Ab × beef breed crossbreeding compared to purebred Ab bulls and through Hereford Hf × beef breed crossbreeding compared to purebred Hf bulls. The data included observations of 8 800 purebred Ab bulls plus Ab × beef breed crosses and 11 815 purebred Hf bulls plus Hf × beef breed crosses. Crossbreeding improved carcass gains and traits compared to purebred Ab and Hf bulls, and production traits improved more by using Continental breeds compared to British breeds. Overall, Continental breeds tended to have carcass traits that suit the Finnish beef production system well under the current Finnish feeding management approach. On the other hand, British breeds produced more intramuscular fat in the meat and had a higher sensory quality compared to Continental breeds. The carcass traits of British breeds can be enhanced for the current market demand by crossbreeding British breed dams with Continental breeds. The grass silage-grain-based diet suited beef breeds well for growing and finishing diets. The concentrate level can be reduced for British breeds. Continental breeds will benefit from increased concentrate levels in the diet. Protein supplementation does not add any substantial advantages to the diet. Using protein supplements will increase the environmental impacts of beef production.
Keywords: beef production; beef bulls; beef breeds; growth performance; carcass characteristics; meat quality